CHINA-JAPAN CONFRONTATION IN THE EAST CHINA SEA AND ITS IMPACT ON ASEAN’S GEOPOLITICAL ARCHITECTURE - Tuan, Nguyen Khoa; Phuong Le, Vu Thi (The Review of International Affairs, 2026)
This article analyzes the impact of the China-Japan confrontation in the East China Sea (2012–2022) on ASEAN’s geopolitical architecture and regional coordinating role. Originating from Japan’s "nationalization" of the Senkaku/Diaoyu Islands in 2012, the China-Japan rivalry transitioned from manageable tensions to protracted strategic confrontation, creating indirect spillover effects on Southeast Asia. The study argues that this complexity stems from the intertwining of geopolitical competition and deep economic interdependence. Applying balance of power theory by Kenneth Waltz, balance of threat theory by Stephen Walt, and hedging strategy, the research demonstrates that ASEAN countries exhibit four stratified response patterns contingent upon threat perception and capacity, while ASEAN faces challenges to its centrality and consensus-building mechanisms yet demonstrates institutional adaptability.